The Factors Associated With The Disobedience Patients To The Medical Treatment Of Positive Smear Pulmonary Tuberculosis At Puskesmas Nganjuk - Lilla Puji; Mandasari, Andita Ayu; Happy, Terza Aflika; Happy, Terza Aflika; Yaner, Nurul Ramadhani; Aprianto, Eko (International Journal of Psychosocial Rehabilitation, 2020)
Tuberculosis as known as TB is an infectious disease directly caused by the bacteria called Mycobacterium tuberculosis. This is still a problem in world health. Disobedience of medical treatment is a dereliction of duty if the person is treated so that it can lead to obstruction of healing. Figures disobedience treatment at Puskesmas Nganjuk 20.1%. This study aims to determine whether, drug side effects, the knowledge, and the PMO are all factors associated with medication non-adherence in patients with pulmonary TB BTA+. This type of research is a quantitative analytical case-control design where samples were taken in a way to count down the number of cases and controls based on the data TB 01 with a sample of 108 samples consisted of 54 sample cases and 54 control samples were carried out at the Regional Public Health Center Nganjuk this research in April and May 2016. The measuring instrument used was a questionnaire. Data analysis to test bivariate with the chi-square test. Results of chi-square tests were done on the side effects of drugs at risk of non-compliance with taking medications obtained p-value 0.000 (OR=9.100). The side effects of drugs is a risk factor for the treatment of non-compliance and the results of the chi -square test of knowledge, PMO is not a factor of disobedience treatment in patients with pulmonary TB BTA+. For patients with pulmonary TB in order to perform the treatment to its conclusion, to say the side effects of drugs that will be taken and pressed so that patients have a close and respected PMO in performing the treatment completely.